1999
DOI: 10.1042/0264-6021:3380083
|View full text |Cite
|
Sign up to set email alerts
|

Brain spectrin (fodrin) interacts with phospholipids as revealed by intrinsic fluorescence quenching and monolayer experiments

Abstract: We demonstrate that phospholipid vesicles affect the intrinsic fluorescence of isolated brain spectrin. In the present studies we tested the effects of vesicles prepared from phosphatidylcholine (PtdCho) alone, in addition to vesicles containing PtdCho mixed with other phospholipids [phosphatidylethanolamine (PtdEtn) and phosphatidylserine] as well as from total lipid mixture extracted from brain membrane. The largest effect was observed with PtdEtn/PtdCho (3:2 molar ratio) vesicles; the effect was markedly sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 29 publications
4
13
0
Order By: Relevance
“…Moreover, the inner monolayer of the erythrocyte membrane contains more PE than PS [87,88]. Such specificity was also seen in the case of non-erythroid spectrin, as reported by Diakowski et al [89], who showed that purified brain spectrin induced an increase in surface pressure in lipid monolayers composed of PE/PC, PS/PC and PC. The strongest effect of spectrin was observed on monolayers containing 50-60% of PE.…”
Section: Spectrin Binds the Phospholipid Bilayersupporting
confidence: 54%
See 3 more Smart Citations
“…Moreover, the inner monolayer of the erythrocyte membrane contains more PE than PS [87,88]. Such specificity was also seen in the case of non-erythroid spectrin, as reported by Diakowski et al [89], who showed that purified brain spectrin induced an increase in surface pressure in lipid monolayers composed of PE/PC, PS/PC and PC. The strongest effect of spectrin was observed on monolayers containing 50-60% of PE.…”
Section: Spectrin Binds the Phospholipid Bilayersupporting
confidence: 54%
“…However, ankyrin inhibited only one of the two possible lipid-binding sites. A similar level of ankyrin-mediated inhibition of lipid interactions was observed for nonerythroid (brain) spectrin [89]. Moreover, it appeared that β-spectrin was inhibited much more strongly than α-spectrin [89,125].…”
Section: Relationship Between Ankyrin-binding and Lipid-binding Activmentioning
confidence: 56%
See 2 more Smart Citations
“…For example, spectrin is known to interact with phosphatidylserine (PS) at multiple sites, and this interaction is mediated by the ␤-subunit. 45,46 Hence, ␤-spectrin polymorphisms could enhance spectrin-PS interactions. Alternatively, polymorphic ␤-spectrin alleles could bind other, currently unknown, integral membrane proteins with differing affinities.…”
Section: Discussionmentioning
confidence: 99%